Proteogenomic Study of the Effect of an Improved Mixed Diet of Live Preys on the Aquaculture of Octopus vulgaris Paralarvae - Varó, Inmaculada; Prado-Álvarez, María; Ortea, Ignacio; Morales, Amalia E.; García-Fernández, Pablo; Domingues, Pedro; Tur, Ricardo; Dios, Sonia; Gestal, Camino (Frontiers in Marine Science, 2022)
The common octopus is the most demanded cephalopod species for human consumption. Despite important advances realized recently, the main bottleneck for commercial production of the common octopus, Octopus vulgaris, is the mass mortality of paralarvae in the first 15–20 days post-hatching (dph), with the main responsible factors still unknown. Thus, the identification of the limiting culture factors is, therefore, crucial for their aquaculture. This study investigates proteomic and transcriptomic responses of octopus paralarvae fed on an improved live preys-mixed diet (M) compared to an Artemia-based (A) reference diet. M diet resulted in the highest paralarvae specific growth rate obtained to date under culture conditions. This is supported by most of the proteins and genes over-expressed in the M group being linked to the cell cycle and replication, production of structural components, and development of the nervous system. Furthermore, the differential nutritional regulation of several genes and proteins seems to indicate that, instead of fatty acids, the preferred fuels for cephalopods would be proteins and carbohydrates. Also, M diet provides a better nutrient balance, which has allowed carrying out this comparative study in paralarvae under optimal conditions at a more advanced stage of growth (20 dph) than in previous studies. Moreover, the paralarvae culture extended up to 40 dph showed for the first time a proper pre-settlement behavior.